(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aims to determine how many crabs are caught in the converted ecosystem area for the construction of the Archipelago Fishing port (PPN). In this study, the analysis will be carried out between the number of crabs caught, the ratio of crabs caught, sex Nisbag, TKG, IKG of mangrove crabs (Scylla serrata). The research was conducted in November 2021 - until February 2022 in the Nusantara Fisheries Port Area - to the mouth of the Maro River. This research uses a descriptive survey method at the research location in the Kali Maro River, Karang Indah Village, the oceanic Fisheries Port area, Merauke District, Merauke Regency. The determination of the location point was carried out by purposive sampling method and based on the abundance of crabs (the location of crab fishing and based on fishermen who often catch crabs at certain location points), the characteristics of each observation area (with 3 different location points). The catch of salaam mangrove crabs in the study was 23, namely 9 males and 14 females. The ratio between male and female crabs at station 1 (one) was 1.2 : 1. At station II (two) between males and females 1: 2.5 and at station III between males and females have a ratio of 0.25: 1. the results of the chi-square test analysis at the 95% confidence interval obtained xÂ² count smaller than the T table and declared insignificant.